Globalização e desenvolvimento regional na Tríplice Fronteira - Eric Gustavo Cardin (Universidade do Vale do Rio dos Sinos (UNISINOS), 2009)
This paper discusses the relationship between the process of globalization and the opportunities for regional development. In order to do that, it theoretically discusses the concepts of globalization, governance and paradiplomacia, noting some of the conflicts and contradictions existing in some of the discussions between skeptical and globalistas. The article also presents empirical considerations by observing the socioeconomic development of the region known as the Triple Frontier (Brazil, Paraguay and Argentina), exploring the interdependence relationship and questioning the contributions that the conceptual discussions bring for the strengthening of reflections referring to local and regional growth.